2018
DOI: 10.3390/en11123477
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Regression Method for Fast Estimation of Solar Irradiation and Photovoltaic Energy Potentials over Europe and Africa

Abstract: In recent years, various online tools and databases have been developed to assess the potential energy output of photovoltaic (PV) installations in different geographical areas. However, these tools generally provide a spatial resolution of a few kilometers and, for a systematic analysis at large scale, they require continuous querying of their online databases. In this article, we present a methodology for fast estimation of the yearly sum of global solar irradiation and PV energy yield over large-scale terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Solar energy should be consumed at a maximum level, particularly in the off-grid areas of Kenya. What makes solar energy preferable to other energy sources is because of the abundant availability of solar radiation in most parts of the country [3]. Kenya's geographical location and open land makes it a high potential for solar farms.…”
Section: Standalone Off-grid Solar Pv Systems In Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…Solar energy should be consumed at a maximum level, particularly in the off-grid areas of Kenya. What makes solar energy preferable to other energy sources is because of the abundant availability of solar radiation in most parts of the country [3]. Kenya's geographical location and open land makes it a high potential for solar farms.…”
Section: Standalone Off-grid Solar Pv Systems In Kenyamentioning
confidence: 99%
“…The study investigated their benefits and challenges, pointing out that they have made it easier to obtain accurate real time solar irradiation data. However, the research concluded that the online tools sometimes provide low-resolution data, in the range of a few kilometers that require multiple queries to the database in case large-scale analysis [3]. This research employs the use of PVGIS database to estimate the potential of electricity production by PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ever-increasing energy demand and rising crude oil prices, as well as predictable expiration of fossil fuels reserves, have also caused high ambitions toward renewable and sustainable energy resources. In this context, renewable energy sources (RES) such as wind and solar are considered as suitable and viable alternative options to generate electrical power [1][2][3][4][5]. However, despite the environmental friendly features of these energies, their dependency on the weather conditions is still a considerable obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic (PV) power generation is the mainstream of solar power generation due to the reduction of PV modules' raw material cost and policy support [1][2][3]. However, the output curve of PV power generation is a semi-envelope shape with a single midday peak due to its intermittence and fluctuation [4].…”
Section: Introductionmentioning
confidence: 99%